2012
DOI: 10.1371/journal.pone.0030878
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Profilin Polymorphism in Pollen with a Focus on Multifunctionality

Abstract: Profilin, a multigene family involved in actin dynamics, is a multiple partners-interacting protein, as regard of the presence of at least of three binding domains encompassing actin, phosphoinositide lipids, and poly-L-proline interacting patches. In addition, pollen profilins are important allergens in several species like Olea europaea L. (Ole e 2), Betula pendula (Bet v 2), Phleum pratense (Phl p 12), Zea mays (Zea m 12) and Corylus avellana (Cor a 2). In spite of the biological and clinical importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 99 publications
(134 reference statements)
8
54
0
Order By: Relevance
“…However, the classification obtained here is in good agreement with the genetic relationships among cultivars already described on the basis of Ole e 1 and Ole e 2 polymorphism (HammanKhalifa et al 2008;Jiménez-López et al, 2012). Moreover, this classification also supports clinical findings describing sharp differences in patient's reactivity to commercially available extracts depending on their place of residence in Spain, where these model cultivars are differentially predominant (Casanovas et al 1997).…”
Section: Clustering Of Cultivars According To Their Relative Allergensupporting
confidence: 90%
See 1 more Smart Citation
“…However, the classification obtained here is in good agreement with the genetic relationships among cultivars already described on the basis of Ole e 1 and Ole e 2 polymorphism (HammanKhalifa et al 2008;Jiménez-López et al, 2012). Moreover, this classification also supports clinical findings describing sharp differences in patient's reactivity to commercially available extracts depending on their place of residence in Spain, where these model cultivars are differentially predominant (Casanovas et al 1997).…”
Section: Clustering Of Cultivars According To Their Relative Allergensupporting
confidence: 90%
“…Previous studies have determined that most allergens isolated and characterized up to date are highly polymorphic (Villalba et al 1993(Villalba et al , 1994Lombardero et al 1994;Asturias et al 1997;Alché et al 1998;Tejera et al 1999;Huecas et al 2001;Martínez et al 2002;Jiménez-López et al 2012). Besides polymorphism, olive cultivars display broad differences in the expression levels for many allergens (Carnés et al 2002;Conde Hernandez et al 2002;Castro et al 2003; as well as in the number and molecular characteristics of the expressed allergen isoforms , 2008Hamman-Khalifa 2005;Castro et al 2010;Jiménez-López et al 2012). These differences are in a certain degree maintained over the years, and have been demonstrated to be associated to the genetic background of the different olive cultivars (Fernandez Caldas et al 2007;Morales et al this volume).…”
Section: Introductionmentioning
confidence: 99%
“…These type of experiential evidences can highlight two important aspects that distinguish the immunological reactivity of profilins: i) profilins are responsible for cross-allergenicity between allergens (recognizable bands in almost all species and/or varieties) and ii) other antibodies are able to recognize subtle differences in the structure between different forms of these molecules (differences in the reactivity of protein bands between species and varieties with different antibodies). In this sense, the observed differences in the reactivity of the extracts of different varieties of olive, seems to support the varietal character as discriminatory parameter in pollen allergens, as clearly was demonstrated for other allergens such as Ole e 1 (Hamman-Khalifa et al 2008), and Ole e 2 (Jimenez-Lopez 2008;Jimenez-Lopez et al 2012) in the case of olive.…”
Section: Molecular Characteristics Of Profilin Explain the Pan-allergsupporting
confidence: 61%
“…In apple (Malus domestica), have been characterized up to 18 genes of Mal d 1, and there is differences in allergenicity depending on the cultivar (Gao et al 2005) which may be due to this extensive allelic diversity. In olive, it has been shown that polymorphism of the allergen Ole e 1 is clearly linked to genetic background (cultivar) (Hamman-Khalifa et al 2008), similarly to what happens to Ole e 2, where there are differential molecular characteristics due to polymorphism, which would be sufficient to explain the differences in reactivity allergenic / immunogenic among profilins from different species, different olive varieties, and even among the same isoforms of profilins (JimenezLopez 2008;Jimenez-Lopez et al 2012). …”
Section: Molecular Characteristics Of Profilin Explain the Pan-allergmentioning
confidence: 99%
“…Epitope prediction based on knowledge from structural derived surface features such as increased solvent accessibility, backbone flexibility, and hydrophilicity were found to correlate well in the present study [19,35,36]. Indeed, contrasting theoretical information about epitopes prediction and available experimental results (IEDB http://www.iedb.org), for allergens analysed in the current study showed that e.g.…”
Section: Discussionmentioning
confidence: 44%